Preliminary study on the feasibility of friction stir welding in 7075 aluminium alloy and polycarbonate sheet - Rahmat, S.M.; Hamdi, M.; Yusof, F.; Moshwan, R. (Maney Publishing, 2014)
Joining of dissimilar materials, especially in the case of polymer and metal, is significantly challenging because of the difference in chemical, mechanical and thermal properties of the materials. In this paper, a feasibility study of dissimilar materials joint between 7075 aluminium alloy and polycarbonate sheet was conducted by using friction stir welding through butt joint. A series of friction stir welding experiments were executed at various levels in order to obtain good joint. The preliminary results indicated that 7075 aluminium alloy and polycarbonate sheet were successfully joined with the aid of frictional heat energy originated from the friction stir welding process. The formation of 7075 aluminium alloy dislocation at the polycarbonate sheet side was clearly observed at the welding interface, which believed to be contributing to the weld strength. The effects of traverse and spindle speed on weld properties as well as the effect of appearance at joint interface are discussed in the paper.